Differences in Achievement Motivation and Its Salient Components Among High and Low Achieving Students - Syeda Salma Hasan , Ruhi Khalid (Pakistan Journal of Psychology, 2012)
This study examined the differences in achievement motivation and its salient components of high and low achieving students. It was hypothesized that high achieving students would have higher achievement motivation and would also score high on the salient components of achievement motivation than low achieving students. Secondly, there would be significant positive correlation between GPA and the components of achievement motivation. A purposive sample of 187 undergraduate students with the distribution of 126 high and 61 low achieving undergraduate students was drawn from three successive academic sessions. Achievement motivation was measured by Helmreich and Spence (1978) work and family orientation scale. Results indicated that high achieving students have significantly higher achievement motivation than low achieving students. Results also indicated that high achieving students are significantly more competitive and work-oriented as compared to low achieving students. However, no significant differences were found between high and low achievers in terms of mastery orientation and personal unconcern. Correlation analysis indicated a significant positive correlation of achievement motivation, competition and work with academic achievement. This study has wider implications for the students, teachers and educationists.